Biochemical characterization of L-asparaginase isoforms from Rhizobium etli—the boosting effect of zinc - Sliwiak, Joanna; Worsztynowicz, Paulina; Pokrywka, Kinga; Loch, Joanna I.; Grzechowiak, Marta; Jaskolski, Mariusz (Frontiers in Chemistry, 2024)
1) The two L-asparaginases, ReAIV and ReAV, encoded by the nitrogen fixing Rhizobium etli, have the same fold, active site, and quaternary structure, despite low sequence identity. 2) ReAIV is about twice as efficient as ReAV in asparagine hydrolysis at 37°C. The activity of both isoforms is boosted by 32 and 56%, respectively, by low concentration of Zn 2+ , which is bound three times more strongly by ReAIV relative to ReAV, as reflected by the Kd values. 3) ReAIV has a temperature optimum at 45-55°C, whereas the activity of ReAV, after reaching its optimum at 37°C, decreases dramatically at 45°C. 4) The divalent cations Hg 2+ , Cu 2+ , Ni 2+ and Cd 2+ have the potential to inhibit both isoforms in the following order (from strongest to weakest inhibitory effect) Hg 2+ > Cu 2+ > Cd 2+ > Ni 2+ . However ReAV is more resistant to Cu 2+ and Cd 2+ , and ReAIV to Hg 2+ and Ni 2+ . Low concentration of Cd 2+ improves the substrate specificity of ReAV and ReAIV, suggesting its role in substrate recognition. The same observation was made for Hg 2+ in case of ReAIV. 5) The activity of the ReAV isoform is less sensitive to Cl -anions, as reflected by the IC50 value for NaCl, which is eightfold higher for ReAV relative to ReAIV.